2007
DOI: 10.1016/j.jsb.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression in Saccharomyces cerevisiae enables isolation and spectroscopic characterization of functional human adenosine A2a receptor

Abstract: The G-protein coupled receptors (GPCRs) are a class of membrane proteins that trigger cellular responses to external stimuli, and are believed to be targets for nearly half of all pharmaceutical drugs on the market. However, little is known regarding their folding and cellular interactions, as well as what factors are crucial for their activity. Further structural characterization of GPCRs has largely been complicated by problems with expression, purification, and preservation of activity in vitro. Previously,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 49 publications
9
94
0
Order By: Relevance
“…As evidence of the essential functions of these proteins, more than half of all drug targets have been shown to be transmembrane proteins, and the analysis of the interactions of transmembrane proteins and their ligands is one of the most promising avenues for the discovery of new drug candidates. As a means of producing sufficient amounts of transmembrane proteins for binding analyses, heterologous protein expression systems have been developed using Escherichia coli (10), yeast (16), insect, and mammalian (4) cells as hosts. Transmembrane proteins generally are expressed at low levels and are extremely hydrophobic, rendering the analysis of interactions with ligands very difficult.…”
mentioning
confidence: 99%
“…As evidence of the essential functions of these proteins, more than half of all drug targets have been shown to be transmembrane proteins, and the analysis of the interactions of transmembrane proteins and their ligands is one of the most promising avenues for the discovery of new drug candidates. As a means of producing sufficient amounts of transmembrane proteins for binding analyses, heterologous protein expression systems have been developed using Escherichia coli (10), yeast (16), insect, and mammalian (4) cells as hosts. Transmembrane proteins generally are expressed at low levels and are extremely hydrophobic, rendering the analysis of interactions with ligands very difficult.…”
mentioning
confidence: 99%
“…J. 2012, 7, 620-634 www.biotechnology-journal.com GFP) followed by a tag optimal for purification (e.g., GFP-His 6 [160] or GFP-His 10 [161]). Tandem affinity purification is an approach where the protein of interest is fused in-frame to two affinity tags, generally separated by a protease cleavage site.…”
Section: Tandem Affinity Purification and Dual-tagging Methodsmentioning
confidence: 99%
“…Previously, we have shown that hA 2 aR is folded in an active, ligand-binding conformation in whole-cell assays, in membrane preparations, and once purified from the cells. 14 present in yeast cells, we would have expected to detect a minimum of 10% of the active complex (B max ) values measured from mammalian controls. Using this as the limit of detection suggests that active A 1 R levels were less than 5 pmol/mg (based on NECA), and for A 3 R, less than 0.2 pmol/mg (IB-MECA).…”
Section: Most Receptors Maintain An Association With Bipmentioning
confidence: 99%
“…14,15,18 Each GPCR was subcloned directly into the pITy-MC-His 10 plasmid 14 and the pITy-MCeGFP-His 10 plasmid. Both vectors contain a multiple cloning (MC) site consisting of EagI, AatII, and SacII immediately following the Gal1-10 promotor and synthetic pre-pro N-terminal leader sequence.…”
Section: Subcloning and Construction Of Gpcr Strainsmentioning
confidence: 99%
See 1 more Smart Citation